Rebuild the Academy: Supporting academic mothers during COVID-19 and beyond - Fulweiler, Robinson W. (PLoS Biol, 2021)
The issues facing academic mothers have been discussed for decades. Coronavirus Disease 2019 (COVID-19) is further exposing these inequalities as womxn scientists who are parenting while also engaging in a combination of academic related duties are falling behind. These inequities can be solved by investing strategically in solutions. Here we describe strategies that would ensure a more equitable academy for working mothers now and in the future. While the data are clear that mothers are being disproportionately impacted by COVID-19, many groups could benefit from these strategies. Rather than rebuilding what we once knew, let us be the architects of a new world.